Amphetamine, past and present – a pharmacological and clinical perspective. (June 2013) - Heal, David J; Smith, Sharon L; Gosden, Jane; Nutt, David J
Amphetamine was discovered over 100 years ago. Since then, it has transformed from a drug that was freely available without prescription as a panacea for a broad range of disorders into a highly restricted Controlled Drug with therapeutic applications restricted to attention deficit hyperactivity disorder (ADHD) and narcolepsy. This review describes the relationship between chemical structure and pharmacology of amphetamine and its congeners. Amphetamine's diverse pharmacological actions translate not only into therapeutic efficacy, but also into the production of adverse events and liability for recreational abuse. Accordingly, the balance of benefit/risk is the key challenge for its clinical use. The review charts advances in pharmaceutical development from the introduction of once-daily formulations of amphetamine through to lisdexamfetamine, which is the first d -amphetamine prodrug approved for the management of ADHD in children, adolescents and adults. The unusual metabolic route for lisdexamfetamine to deliver d -amphetamine makes an important contribution to its pharmacology. How lisdexamfetamine's distinctive pharmacokinetic/pharmacodynamic profile translates into sustained efficacy as a treatment for ADHD and its reduced potential for recreational abuse is also discussed.